Endocrown as a rehabilitative treatment in primary molar with pulpectomy. Case report - Palomino - Ríos, Ethel (2020)
The purpose of performing an endocrown as a rehabilitative treatment of a primary molar, maintaining its integrity and keeping it in its space.The methodology used was the report of a clinical case in a 2-year-old, 10-month-old male patient, with prior treatment of pulpectomy in one of his molars, which was subsequently rehabilitated with an endocrown. In the clinical evaluation at 4 and 12 months, the 16 evaluation criteria were used for direct and indirect restorations according to the World Dental Federation, which are divided into 3 groups and were found to meet the criteria of brightness and roughness, color matching, anatomical shape, retention, marginal adaptation; integrity of surrounding teeth, periodontium and adjacent mucosa. He did not present a caries fracture and recurrence.So it would be a treatment option in pediatric dentistry because of its simple technique, but more studies and follow-ups are required to determine its long-term advantages.